Baby on board: pregnancy as a source of conflict for the psychiatry registrar. (April 2013) - Hamilton, Laura
Objective: A literature review explores the author's experience of conflict while working as a psychiatry registrar during her pregnancy. Conclusions: Conflicts may arise during a registrar's pregnancy, but can be mediated through effective supervision and peer support, and may benefit future clinical practice with the development of new insights and enhanced self-awareness.